EVALUATING THE EFFECTIVENESS OF HOSPITAL MANAGEMENT INFORMATION SYSTEMS ON SERVICE PERFORMANCE: A QUALITATIVE SYNTHESIS BASED ON THE INFORMATION SYSTEM SUCCESS MODEL - Carens Sintha Iralin De Ivanka; Ellen Angelique Hardjono; Kathlyn Allysha; Timotius Gavriel Kristo; Kosasih (International Archives of Medical Sciences and Public Health, 2026)
This study analyzed the effectiveness of Hospital Management Information System (SIMRS) implementation in improving hospital service performance by examining the interaction between technological, human, and organizational dimensions. A qualitative literature synthesis with a conceptual narrative review design was employed by integrating secondary data from scientific journals, academic books, and health information system policy documents. Data were analyzed using qualitative content analysis guided by the De Lone and McLean Information System Success Model and enriched with a socio-technical systems perspective. The synthesis showed that SIMRS implementation improved service efficiency, data accuracy, inter-unit coordination, and decision-making quality through better system quality, information quality, and service quality. However, its effectiveness depended on system-user alignment, digital competence, infrastructure readiness, and organizational support. Poor alignment between system design and actual work practices may reduce adoption and encourage workarounds. Therefore, SIMRS should be implemented holistically by balancing technical infrastructure, user capacity building, and adaptive organizational governance.